Empowering Moral Values: The Role of Pencak Silat Tapak Suci in Moral Internalization through Extracurricular Activities - Putri Damayanti (Cahaya Ilmu Cendekia Publisher, 2024)
Purpose of the study: This research was conducted with the aim of finding out 1) what moral values are contained in the Pencak Silat extracurricular at Tapak Suci at State Islamic Senior High School 1 Semarang, 2) how the internalization of the moral values contained in the extracurricular Pencak Silat at Tapak Suci at State Islamic Senior High School 1 Semarang. Methodology: This researcher uses a qualitative field approach using descriptive analysis techniques. Data collection uses interview, observation and documentation methods. Main Findings: The results of this research are: 1) There are four basic moral values ​​contained in the Tapak Suci pencak silat extracurricular at State Islamic Senior High School 1 Semarang. Namely a) morals towards Allah, b) morals towards fellow humans, c) morals towards the environment and d) morals towards oneself. 2) The stage and process of internalizing moral values in the Tapak Suci pencak silat extracurricular is through three stages, namely a). Introduction and understanding, b) Acceptance stage, c) Internalization stage. Internalizing these moral values aims to bring about changes in the moral values of students. Novelty/Originality of this study: Novelty from study This that is study about values morals that can be taken from extracurricular pencak martial arts footprint holy. With study This can conserve culture so No faded by the times.